2017
DOI: 10.1177/2396987317703210
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Explanations for Cryptogenic Stroke in the Young: Revealing the Triggers, Causes, and Outcome (SECRETO): Rationale and design

Abstract: Background: Worldwide, about 1.3 million annual ischaemic strokes (IS) occur in adults aged <50 years. Of these early-onset strokes, up to 50% can be regarded as cryptogenic or associated with conditions with poorly documented causality like patent foramen ovale and coagulopathies. Key hypotheses/aims: (1) Investigate transient triggers and clinical/sub-clinical chronic risk factors associated with cryptogenic IS in the young; (2) use cardiac imaging methods exceeding state-of-the-art to reveal novel sources f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
0
37
1
1
Order By: Relevance
“…Revealing the Etiology, Triggers, and Outcome study (SECRETO, NCT01934725), which is an international prospective multicentre case-control study of young adults (age 18-49) with a first-ever ischaemic stroke of undetermined aetiology. The study protocol has earlier been published in more detail (Putaala et al, 2017).…”
Section: Study Populationmentioning
confidence: 99%
“…Revealing the Etiology, Triggers, and Outcome study (SECRETO, NCT01934725), which is an international prospective multicentre case-control study of young adults (age 18-49) with a first-ever ischaemic stroke of undetermined aetiology. The study protocol has earlier been published in more detail (Putaala et al, 2017).…”
Section: Study Populationmentioning
confidence: 99%
“…Searching for Explanations for Cryptogenic Stroke in the Young: Revealing the Etiology, Triggers, and Outcome (SECRETO; NCT01934725) is an international prospective multicenter case-control study of young adults (age 18-49) presenting with an imaging-positive first-ever ischemic stroke of undetermined etiology. The main study protocol has been published in more detail previously [13]. Briefly, patients are included after standardized and timely diagnostic procedures, including brain magnetic resonance imaging, imaging of intracranial and extra-cranial vessels with either computed tomography angiography or magnetic resonance angiography, and cardiac imaging to rule out established causes of ischemic stroke.…”
Section: Study Populationmentioning
confidence: 99%
“…As a major strength, our case-control study was based on prospectively enrolled patients with thorough baseline characterization for both cases and controls, including structural and standardized echocardiography protocol [13,14]. Another strength is that the semi-automatic assessment of non-compacted LV mass was highly reproducible, probably due to only minor manual corrections.…”
Section: Plos Onementioning
confidence: 99%
“…Although ischemic stroke is not common in the young population, 10-15% of all ischemic stroke events occur in patients 18-50 years of age [ 6 ]. Globally, the annual incidence of ischemic stroke is 1.3 million in adults <50 years of age [ 7 ]. Recent studies have suggested that ischemic stroke in younger patients increases along with an increase in traditional risk factors commonly associated with stroke in older adults [ 6 ].…”
Section: Introductionmentioning
confidence: 99%